(untitled) (mathematica didactica, 2002)
Today there are only two main roles of geometry in public education left: fostering reflected visual perception and promoting heuristic problem solving. These two functions rise some problems, which are yet unsolved or at least not satisfactory clarified: The interrelations of plane and spatial geometry should be analysed and redesigned under didactical points of view. After the decline of classical formation on the grounds of Platon and Euclid the traditional formal language of geometry needs no longer be separated from daily colloquial language. The core of conceptual knowledge in geometry can be secularized, and it has to be from sociological and from some fashionable constructivistic viewpoints. On the other side modern „elementary“ spatial geometry should comprise an adequate language for processual movements and timedependend processes in general.